CLAY AND COMPARATIVE MATERIAL ANALYSIS THROUGH XRD AND PETROGRAPHY FOR KUNTUR WASI, CAJAMARCA, PERU - Druc, Isabelle (2013)
X-ray diffraction and petrographic analyses of soils, clays and tempers collected around the archaeological site of Kuntur Wasi, near San Pablo, in the northern Peruvian Andes, aim at investigating the composition of local materials and the possibility of on-site production. The results of the XRD study shows that the analyzed clay found around the site is an illite, while the other collected soils from San Pablo are not clays of ceramic production range. The volcanic temper used by modern potters eight kilometers north of the archaeological site is very similar to the temper observed in many of the ancient ceramics from Kuntur Wasi. Also, analysis of clays from the middle Jequetepeque valley shows the presence of kaolin, which is absent from the analyzed clays in the Kuntur Wasi region.